TO REPORT A CASE OF UNILATERAL PAPILLITIS IN A YOUNG FEMALE - VIPUL SIDHARTH,; REENA KUMARI,; DINESH KUMAR BHAGAT, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purpose of the study is to report a case of unilateral papillitis in a young female. Methods: A 13-year-old girl presented in our outpatient department with sudden, painful, and progressive diminution of vision in the left eye for the past 7 days. The best-corrected visual acuity in R/E was 6/6 and in L/E was FC 5 m. On slit-lamp examination of the anterior segment, RAPD was present in L/E and rest findings were within normal limits. Fundus examination of R/E was within normal limits and of L/E – blurred disc margin, elevated disc, hyperemic disc, flame-shaped hemorrhages along superior arcuate vessels, retinal vessels were tortuous and foveal reflex was present. The case was evaluated with optical coherence tomography, Goldmann applanation tonometer, and color vision test (Ishihara test). Ocular movements were at full range. Results: Retinal imaging of L/E showed blurred disc margin, elevated disc, hyperemic disc, flame-shaped hemorrhages, tortuous retinal vessels, and foveal reflex present and of R/E, CD ratio – 0.3, retinal vessels – normal, and foveal reflex – present. Intraocular pressure on Goldmann applanation tonometer was 16 mmHg in R/E and 18 mmHg in L/E. A color vision test showed severely impaired color vision in her L/E. Conclusion: Papillitis refers to the involvement of the optic disc in inflammatory and demyelinating disorders of the optic nerve. The patient was counseled regarding the nature of lesion and rare incidence of complications such as postneuritic optic atrophy leading to complete blindness in case of a recurrent attack of papillitis. Optic neuritis treatment trial was started and significant improvement in visual acuity and fundus findings were seen.